AN ANALYSIS OF CONVERSATIONAL IMPLICATURE IN THE INTERVIEW MOVIE - Ines Seri Pinta Uli Butar Butar and Muhammad Natsir (LINGUISTICA, 2016)
The study was deal with the types of conversational implicature occur in the utterances of all of the characters in The Interview Movie. The objectives of the study were to identify and classify the types of conversational implicature and explain the reason why it becomes the dominant type that occur in the movie. The data was analyzed by identifying the utterances found in the movie script. The findings shows that the two types of conversational implicature were occurred in the movie. The characters conveyed an implicit meaning when giving statement or opinion or information and answering the question in their conversation based on the truth condition or facts in the movie so that the viewers can draw assumption from the implicit meaning of the utterances all the characters.